Simulation and implementation of an induction motor speed control system using the Oriented Field technique - Rodríguez Valdez, Carlos (2003)
In this work, a Field Oriented Control (FOC) scheme is developed for the speed of an induction motor. It begins with a brief history of the fundamental ideas that allowed the development of this type of control; what's nextis the study of the general principles of FOC. Below is an equivalent model of the induction motor associated with the FOC system; Next, simulation and implementation results are shown in which it is expected to observe the decoupling of the currents in field coordinates, the behavior ofthe stator currents, the very fast response of the electrical torque and the stable behavior of the speed, both in vacuum and in the presence of load. Finally, observations and conclusions relevant to this research are provided.